Analysis of the Influence of Micro, Small and Medium Business Growth on Poverty Reduction in 5 ASEAN Countries - Ernestus Florian Lamaile; Nuning Trihadmini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This study aims to analyze the effect of micro, small and medium (SME) growth on poverty alleviation in 5 ASEAN Countries with the research period 2010-2019. The sample of this study is 5 ASEAN countries, namely Indonesia, Myanmar, Philippines, Thailand, and Vietnam. The dependent variable in this study is poverty as measured by the proportion of the population living below the international poverty line, in terms of the number of monetary units to meet the minimum living needs. This study uses the Panel Data method and the results show that there is significant relationship between MSME growth, the Trade Openness Index, per capita income growth, and the Human Development Index on poverty alleviation in 5 ASEAN countries.